2015
DOI: 10.3906/sag-1309-62
|View full text |Cite
|
Sign up to set email alerts
|

The patterns and clinical relevance of contact allergen sensitization in a pediatric population with atopic dermatitis

Abstract: Background/aim: Data about contact allergen sensitization (CAS) in children with atopic dermatitis (AD) are limited. The purpose of this study was to identify the frequency and patterns of CAS in children with AD by using a ready-to-use patch test system. Materials and methods:After receiving the history of CAS in the patients, the severity of AD and IgE-mediated allergen sensitization were determined.Results: Of 134 children with AD, 33.8% (n = 45) had at least 1 positive reaction. The most frequent positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
16
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
9
16
1
1
Order By: Relevance
“…In previous studies an association between AD and contact allergy to topical corticosteroids was suggested . It does not seem to constitute a significant problem among children with AD, although delayed positive reactions may have been missed in the reviewed studies . In the study by Mailhol et al ., only one of 641 children reacted to one of the corticosteroid markers.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In previous studies an association between AD and contact allergy to topical corticosteroids was suggested . It does not seem to constitute a significant problem among children with AD, although delayed positive reactions may have been missed in the reviewed studies . In the study by Mailhol et al ., only one of 641 children reacted to one of the corticosteroid markers.…”
Section: Discussionmentioning
confidence: 93%
“…Although the correlation was not significant, the authors found the lowest frequency of contact sensitization among children with severe AD (13·9%), compared with children with moderate (55·6%) and mild (30·6%) AD. Akan et al . found no association between the severity of AD and the overall risk of contact sensitization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations